Millimeter-Wave (mmWave) Communications - Sanchez, Manuel García (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The millimeter-wave frequency band (30-300 GHz) is considered a potential candidate to host very high data rate communications. First used for high capacity radio links and then for broadband indoor wireless networks, the interest in this frequency band has increased as it is proposed to accommodate future 5G mobile communication systems. The large bandwidth available will enable a number of new uses for 5G. In addition, due to the large propagation attenuation, this frequency band may provide some additional advantages regarding frequency reuse and communication security. However, a number of issues have to be addressed to make mm-wave communications viable. This book collects a number of contributions that present solutions to these challenges.